Organizational stressors and job stress among Malaysian managers: the moderating role of personality traits - Kumaresan V. Sathasivam; Mohd Dahlan Hj. A. Malek; Ahmad Faris Abdullah (Macrothink Institute, 2015)
Job stress is vastly present in today’s organizations, and the costs of these phenomena cut across all levels of society. In recent years, researchers considering job stress in the workplace have made great strides in understanding several aspects of the stress phenomenon in the field of organizational behavior. Thus, it becomes more important that the individual variables of these job stresses are well explored and directly linked to individuals experiencing this situation, in order to ensure the right stressors are well understood and other moderating functions are studied, like the personality variables. This research presents an integration of past research and theory that models the relationship of organizational stressors like conflict, work overload, unfavorable work condition, and the moderating role of personality traits among managers. The scope of this study is limited to managerial positions in electronics firms in Malaysia. A set of demographic factors like gender, marital status and educational background, are also studied as influencing factors to job stress. The final framework in this study includes the organizational stressors as the independent variable and job stress as the dependent variable, with the personality traits moderating that relationship. A proportional sampling plan will be done to cover the surveys to be covering all major locations of electronics firms in Malaysia. Theoretical and managerial implications of the study will be discussed in details. The implication of the study would be extremely beneficial for electronics organizations in not only identifying the organizational sources of job stress, but also to understand the personality behaviors of their management staffs and how that related to job stress. Organizational stressors play a big role in the study, in which understanding its influence to job stress and how to manage and cope would enable the leadership team in the electronics organizations to be able to handle job stress more efficiently.